Diagnosis, treatment, and genetic characteristics of blastic plasmacytoid dendritic cell neoplasm: A review. Issue 7 (17th February 2023) - Wang, Yemin; Xiao, Li; Yin, Lili; Zhou, Lv; Deng, Yanjuan; Deng, Huan
Abstract : Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a highly aggressive and extremely rare hematologic disease with a poor prognosis, involving mainly the skin and bone marrow. The immunophenotype of these tumor cells is characterized by the expression of CD4, CD56, CD123, TCL-1, and CD303. To date, no consensus has been reached on the standard of care for BPDCN. Currently, clinical treatment is mainly based on high-dose chemotherapy combined with hematopoietic stem cell transplantation. However, this treatment method has limitations for elderly, frail, and relapsed/refractory patients. In recent years, breakthroughs in molecular biology and genetics have not only provided new ideas for the diagnosis of BPDCN but also helped develop targeted treatment strategies for this disease. The emergence of targeted drugs has filled the gap left by traditional therapies and shown great clinical promise. This article focuses on the latest advances in genetics and targeted therapies for BPDCN, especially the emerging therapies that may provide new ideas for the clinical treatment of BPDCN.